Porosity and Dimensional Changes in Cu and Cu-Ni System - Abdul-Razzaq Ismail Kheder (Engineering and Technology Journal, 1977)
The porosity formed during interdiffusion in OFHC Cu/Ni diffusion couples, and in OFHC Cu discs and cylinders due to hydrogen have been studied. Different volumes of porosity and dimensional changes were obtained after diffusion annealing in vacuum and in 1 atm argon gas under similar conditions. Porosity introduced previously in OFHC Cu prior to welding to Ni affected the subsequent porosity during diffusion annealing. Prestraining of specimens showed extensive porosity but with reduced sizes. These observations can creat problems in many engineering areas such as coating of materials, welding of dissimilar materials, composite materials and where fine tolerances are required.